The successful use of polylactide wound dressings for chronic lower leg wounds: A retrospective analysis. Issue 5 (8th November 2021) - Nischwitz, Sebastian P.; Popp, Daniel; Shubitidze, David; Luze, Hanna; Zrim, Robert; Klemm, Klaus; Rapp, Matthias; Haller, Herbert L.; Feisst, Manuel; Kamolz, Lars‐Peter
Abstract: Chronic wounds are a challenging medical entity for patients, medical professionals and healthcare systems. Frequently, patients present themselves to wound specialists after months or even years of unsuccessful treatment. Recent developments have resulted in a multitude of different advanced wound dressings created to treat complex, chronic wounds, one of which is the polylactide dressing Suprathel. This study aimed at investigating the healing potential of Suprathel in chronic wounds and differentiating between old and "young", diabetic and non‐diabetic chronic wounds. A prospective, multicentric, non‐controlled intervention study was conducted, treating patients with chronic lower leg ulcers (>3 months) with Suprathel and assessing them weekly. Afterwards, a retrospective analysis was performed analysing the wound size initially, after 4 and after 8 weeks of treatment. Furthermore, a differentiation between diabetic and non‐diabetic, and chronic wounds older and younger than 12 months, was assessed. A significant reduction in wound size was observed in the study population after 8 weeks of treatment. The effect size in the diabetic wound and the old chronic wound group even reached more than one, with the other groups still showing a large effect of the intervention. This study shows that Suprathel is a valuable tool in the armamentarium of a wound specialist. Not only could we show a positive effect on chronic wounds, we could even demonstrate a significant wound size reduction in chronic wounds of old and young, as well as diabetic wounds, with the treatment of older chronic and diabetic wounds yielding an even larger effect size. Further randomised, controlled studies are necessary to show the full potential of advanced wound dressing materials in large patient cohorts.